2019
DOI: 10.1002/jcp.29248
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related neurodegenerative diseases

Abstract: Converging evidence indicates the dysregulation of unique cytosolic compartments called stress granules (SGs) might facilitate the accumulation of toxic protein aggregates that underlie many age‐related neurodegenerative pathologies (ANPs). SG dynamics are particularly susceptible to the cellular conditions that are commonly induced by aging, including the elevation in reactive oxygen species and increased concentration of aggregate‐prone proteins. In turn, the persistent formation of these compartments is hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 132 publications
(137 reference statements)
0
10
1
Order By: Relevance
“…The effect of BAG3 on SGs and its role in neurodegenerative disorders was recently reviewed by Duggan et al [499].…”
Section: Stress Granules and Defective Ribosomal Productsmentioning
confidence: 99%
“…The effect of BAG3 on SGs and its role in neurodegenerative disorders was recently reviewed by Duggan et al [499].…”
Section: Stress Granules and Defective Ribosomal Productsmentioning
confidence: 99%
“…Multiple scientific reports suggest that under normal physiological conditions a microtubule-associated protein tau (MAPT) is sensitive to autophagy-associated ubiquitin-binding protein p62/SQSTM1, which promotes degradation of the misfolded, microtubule-dissociated tau protein. However, in tauopathy, an insoluble form of mutant MAPT becomes resistant to recognition by and binding to p62/SQSTM1 and as a result, fails to degrade inside autophagosomes [6]. This study revealed that the pathology caused by the intracellular formation of neurofibrillary tangles (NFTs) by the hyperphosphorylated form of mutant MAPT, can be suppressed by p62/SQSTM1 overexpression resulting from delivery of AAV 2/9-SQSTM1 expression vector.…”
Section: Selection Of Optimal Gene Therapy Strategymentioning
confidence: 90%
“…A significant determinant of NDD progression is an accumulation of toxic proteins on a subcellular level [5,6]. Intracellular accumulation of specific abnormally-aggregated proteins in the form of inclusion bodies is associated with different pathologies of most common NDDs: while Alzheimer's destroys memory, Parkinson's and Huntington's diseases affect movement.…”
Section: Introductionmentioning
confidence: 99%
“…PTMs exist naturally in the human body and participate in many physiological functions such as cell differentiation and gene regulation. However, at high concentrations, they may indicate serious diseases, such as myocardial infarction, venous thromboembolism, arterial and venous thrombosis, pulmonary embolism, and cancer [141][142][143][144][145], and emerge as important markers of aging and aging-related diseases [146,147]. Compared with blood, urine is non-invasive and easy to collect.…”
Section: Discussionmentioning
confidence: 99%